1998
DOI: 10.1046/j.1464-410x.1998.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of power Doppler ultrasonography in the diagnosis of acute pyelonephritis

Abstract: Objective  To assess the ability of power Doppler ultrasonography (PDU) to detect acute pyelonephritis and to compare the findings from PDU with those from enhanced computed tomography (CT). Patients and methods  Eleven patients (mean age 18.5 years, range 5–37) admitted to hospital with a clinical diagnosis of pyelonephritis were assessed with PDU and enhanced CT, the latter providing the reference method. Results  The imaging studies showed normal findings in three patients; a single focus of pyelonephritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
8

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
0
12
0
8
Order By: Relevance
“…More recent studies have shown that PDS has fairly high sensitivity and specificity for the evaluation of APN and is superior to color Doppler sonography. [22][23][24] Although the lack of ionizing radiation or contrast injection is the advantage of PDS, it is a time-consuming procedure and is difficult to Patients with…”
Section: A C D B E F Discussionmentioning
confidence: 99%
“…More recent studies have shown that PDS has fairly high sensitivity and specificity for the evaluation of APN and is superior to color Doppler sonography. [22][23][24] Although the lack of ionizing radiation or contrast injection is the advantage of PDS, it is a time-consuming procedure and is difficult to Patients with…”
Section: A C D B E F Discussionmentioning
confidence: 99%
“…I u svojoj studiji Dell Atti L. [13] pokazuje da sa senzitivnošću od 76 %, i specifičnošću od 75 %, upotreba Dopler ultrazvuka je velika i nezaobilazna u dijagnostikovanju i praćenju akutnog pijelonefritisa. Nadalje, u studiji Sakarya ME i saradnika [14] uloga Dopler ultrasonografskog ispitivanja akutnog pijelonefritisa je nezaobilazna sa senzitivnošću od 88% i kompletnom specifičnošću. Mada u studiji koju su radili Berro Y i autori, [15] ukazano je da je Dopler ultrasonografsko ispitivanje korisno u dijagnostikovanju, ali nedovoljno da zameni DMSA scintigrafiju.…”
Section: Tabela 8 Ultrasonografski Parametri Koji Ukazuju Na Akutni unclassified
“…US presents a much lower sensitivity than CT [35,36], revealing some pathological features just in 40% of subjects with a positive CT [37]. US may reveal renal enlargement with a reduced visibility of renal sinus which appears focally or diffusely compressed, especially in young patients since in adults nephrosclerosis may be present.…”
Section: Acute Renal Infectionsmentioning
confidence: 99%
“…Renal and perinephric abscesses may appear as fluid collections or as complex lesions with or without layers of debris or air. In children and young adults CD and PD analysis increase the sensitivity of US in detecting acute pyelonephritis up to 63% [38,39,40] by revealing single or multiple hypoperfused renal regions determined by inflammatory oedema (Fig. 9).…”
Section: Acute Renal Infectionsmentioning
confidence: 99%